Impact of joint commission international accreditation on occupational health and patient safety: A systematic review - Anni Vuohijoki; Leena Ristolainen; Juhana Leppilahti; Sanna-Maria Kivivuori; Heikki Hurri (PLoS ONE, 2025)
Objectives To illuminate the benefits of Joint Commission International (JCI) accreditation and other experiences related to the accreditation process in relation to occupational health and patient safety. Design Systematic review Methods We systematically searched CINAHL (n = 77), ProQuest (n = 69), PsycINFO (n = 13), PubMed (n = 166), and Scopus (n = 211) for articles on JCI accreditation published until December 2023. Overall, 290 articles were found. JCI-accredited hospitals with before–after accreditation follow-up processes, hospitals during the accreditation process, and job satisfaction and/or patient safety as the primary outcome measures were included. Non-original articles, articles including non-accredited hospitals, hospitals missing before–after accreditation changes, studies with no follow-up time, hospitals implementing accreditation guidelines but not accredited, non-English publications, reviews, meta-analyses, master theses, and poor-quality studies were excluded. Results Two authors independently applied the above criteria, following which 16 articles were analyzed. Two of these, however, were further excluded due to poor quality; 14 articles were finally included. All the articles were extremely heterogeneous, leaving no possibility for a meta-analysis. Conclusions The impacts of accreditation are significant in underdeveloped than in developed nations where the legal requirements are high. Concerns regarding costs and workload associated with accreditation processes are increasing. Moreover, studies regarding JCI accreditation and its impact on occupational health or patient safety are limited, thus warranting further investigations. PROSPERO registration number: CRD42021275665.